2009
DOI: 10.1080/13803610902955333
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive development in Dutch primary education, the impact of individual background and classroom composition

Abstract: A sample of 815 Dutch pupils from 49 classes was followed from age 6 (Dutch Grade 3) through age 11 (Grade 7) to estimate growth trajectories for pupils with different socio-ethnic backgrounds. The results indicate that the disadvantage for spelling already present in Grade 3 increases more strongly for Dutch lowsocioeconomic status (SES) pupils than for low-SES minority pupils. With regard to mathematics, the initial disadvantage of Dutch low-SES pupils hardly changes, whereas the gap is clearly reduced for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
(35 reference statements)
1
17
0
1
Order By: Relevance
“…Indeed, longitudinal studies investigating school composition have demonstrated differential school composition effects on achievement on the first measurement occasion and subsequent learning growth. Most of these studies have found significant school composition effects on achievement on the first measurement occasion and no or considerably smaller school composition effects on learning growth (Belfi et al, 2013;Guldemond & Bosker, 2009;Luyten, Schildkamp, & Folmer, 2009;Verhaeghe et al, 2011).…”
mentioning
confidence: 93%
“…Indeed, longitudinal studies investigating school composition have demonstrated differential school composition effects on achievement on the first measurement occasion and subsequent learning growth. Most of these studies have found significant school composition effects on achievement on the first measurement occasion and no or considerably smaller school composition effects on learning growth (Belfi et al, 2013;Guldemond & Bosker, 2009;Luyten, Schildkamp, & Folmer, 2009;Verhaeghe et al, 2011).…”
mentioning
confidence: 93%
“…This study adds to the existing research in three ways. First, previous studies on differences in the language growth trajectories of different pupil groups have focused on one language domain only, namely, reading fluency (McCoach et al ., ), spelling (Luyten et al ., ), reading comprehension (Droop & Verhoeven, ), or language achievement generally (Hill & Rowe, ; Guldemond & Bosker, ). The same limitation holds for most research on school composition effects (Driessen, ; Van der Slik et al ., ; Guldemond & Bosker, ).…”
Section: Introductionmentioning
confidence: 99%
“…As noted, the model examining the effect of the metric spans 1998 to 2001, while the model evaluating the impact of the assessment spans 2002-2004. It is important to consider the specification of Equation (1) carefully considering that previous research suggests that student growth in terms of academic achievement does not necessarily follow a linear pattern over time (Guldemond & Bosker, 2009;Luyten, Schildkamp, & Folmer, 2009;Seltzer et al 1994; Van der Werf, Opdenakker, & Kuyper, 2008). Both Luyten et al (2009) and Guldemond and Bosker (2009) demonstrated that student cognitive growth is characterized most appropriately with a nonlinear growth trajectory.…”
Section: Methodsmentioning
confidence: 97%
“…It is important to consider the specification of Equation (1) carefully considering that previous research suggests that student growth in terms of academic achievement does not necessarily follow a linear pattern over time (Guldemond & Bosker, 2009;Luyten, Schildkamp, & Folmer, 2009;Seltzer et al 1994; Van der Werf, Opdenakker, & Kuyper, 2008). Both Luyten et al (2009) and Guldemond and Bosker (2009) demonstrated that student cognitive growth is characterized most appropriately with a nonlinear growth trajectory. Moreover, Van der Werf et al (2008) showed that, even though student growth trends may be linear on average, the size of the quadratic term can vary significantly between schools; thus, quadratic growth curves could be a better fit for the data for some schools but not for others.…”
Section: Methodsmentioning
confidence: 97%